Honorarium, Aktris, Gender: Perempuan Pekerja Seni dalam Industri Perfilman Indonesia, 1950an-1970an - Indira Ardanareswari (Universitas Gadjah Mada, 2018)
Observing women as art workers, one can’t put away how women contribute to promote popular entertainment art such as movie. Women in the movie industry between 1950’s until 1970’s held extremely important roles. Big demands of women have given them freedom to participate in the works, choosing professions in the movie industry based upon their respective passion. In the development, they began to be driving forces of the expansion of public spaces for women in their locality, especially within the movie industry. These actresses were promoted intensively as a way to legitimate commercial movies. Apart from earning proper wages, they also were widely exposed but also objectified.